THE STEPS MODEL AND STAKEHOLDERS TO OBSERVE INTENSITY OF PARTICIPATION IN THE NEW PUBLIC GOVERNANCE - TORRES DE OLIVEIRA, ANTONIA DANNIELE JESKA; Santaella Gonçalves, Rodrigo (RP3 - Revista de Pesquisa em Políticas Públicas, 2025)
Abstract This article investigates the level of participation in public policies shaped by New Public Governance, focusing on assessing the democratic quality of decision-making processes in climate governance. The central question is: Can mapping decision-making across the phases of a public policy create a tool for measuring participation intensity through stakeholder analysis and social network mapping? The study hypothesizes that the steps model of public policy and the concept of “Participation Intensity” can serve as effective tools for monitoring democratic engagement within governance-based public policies. The theoretical framework applies public policy cycle theory to decision-making, enabling the development of a representative model that highlights participatory processes within public policy. Methodologically, the study combines bibliographic research with empirical applications, tracing the historical evolution of the public sector—divided into Classical and Contemporary periods. It applies the staged model of public policy cycle theory to elements of New Public Governance, focusing on consortia and public–private partnerships (PPPs) in solid waste management policy, with illustrative case studies in Brazil and Sweden. The results reveal varying levels of participation intensity across the cases, suggesting that the use of social network maps to analyze policy stages offers valuable insights into the context and challenges of democracy, decision making processes and participation in public policy. By delineating actors and mapping their relationships, this approach provides a practical framework for examining democratic processes in governance-based public policy.